1998
DOI: 10.1021/jp981524c
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of the Sodium/12-Crown-4 Complex:  Photoionization and ab Initio Molecular Orbital Studies

Abstract: The molecular complexes formed between sodium atoms and 12-crown-4 molecules were generated in a flow reactor and studied with photoionization mass spectroscopy. The photoionization threshold energies of these complexes, which are dependent on the complex conformations, were obtained from the analysis of the photoionization efficiency spectra. Ab initio molecular orbital calculations were performed on the possible conformers of these complexes and their corresponding ionic states. With the help of theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Generally speaking, for the diol complex, the HF ionization energies are lower than the corresponding MP2 energies by about 0.15 eV and the MP2 energies are in turn less than the corresponding B3PW91 values by about 0.23 eV. Since it has been demonstrated that the ionization energies calculated by the B3PW91 method are in better agreement with the experimental measurements, , the B3PW91 ionization energies shall be adapted exclusively for the following discussion on the ionization energies. The HF and MP2 ionization energies are served as references.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally speaking, for the diol complex, the HF ionization energies are lower than the corresponding MP2 energies by about 0.15 eV and the MP2 energies are in turn less than the corresponding B3PW91 values by about 0.23 eV. Since it has been demonstrated that the ionization energies calculated by the B3PW91 method are in better agreement with the experimental measurements, , the B3PW91 ionization energies shall be adapted exclusively for the following discussion on the ionization energies. The HF and MP2 ionization energies are served as references.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the experimental setup, which mainly consists of a photoionization mass spectrometer coupled with a flow reactor, have been described in previous publications. , In the following, only the experimental conditions, which were relevant to the present experiment, are mentioned briefly. The sodium vapor was generated in an oven heated to 616 K. An argon flow, which constituted a partial pressure of about 570 mTorr in the flow reactor, carried the sodium vapor into the flow tube and reacted with diol vapor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations